CCR6 is transiently upregulated on B cells after activation and modulates the germinal center reaction in the mouse. Issue 5 (16th April 2013) - Wiede, Florian; Fromm, Phillip D; Comerford, Iain; Kara, Ervin; Bannan, Jennifer; Schuh, Wolfgang; Ranasinghe, Charani; Tarlinton, David; Winkler, Thomas; McColl, Shaun R; Körner, Heinrich
Abstract : The CC‐chemokine receptor 6 (CCR6) is expressed constitutively at an intermediate level on naïve B cells and is upregulated after activation on pregerminal center (GC) B cells. We hypothesized that it could be involved in the events leading to GC reaction and high‐affinity antibody production, and therefore investigated the potential role of CCR6 in B‐cell differentiation in vivo . After antigenic challenge of CCR6 −/− mice with the T‐cell‐dependent antigen nitrophenyl‐keyhole limpet hemocyanin (NP‐KLH), GC B‐cell development was found to be accelerated and the number of GC had increased significantly compared with control mice, but the antibodies produced by CCR6 −/− B cells were on average of lower affinity. We conclude from these data that the CCR6/CCL20 axis has an important role in regulating the kinetics and efficiency of the GC reaction.